Sumber-Sumber Hukum Islam - Arofik, Slamet; Rofiah, Ayu Fadlilatur (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2023)
Fiqh is a "new discovery" that arises from the interpretation of the texts of the Qur'an and Hadith that have Dzanny al-Dilalah nature and from new matters that have never been the object of study before. Examining Fiqh cannot be separated from studying and analyzing the sources of legal rulings, commonly known as Mashadir al-Shari'ah or Mashadir al-Ahkam al-Shar'iyyat (sources of Islamic law). Typically, in the books of Usul al-Fiqh, it is mentioned that the sources of Islamic law or Adillah al-Shar'iyyah can be broadly grouped into two categories: sources agreed upon/recognized by the majority of scholars (Muttafaq 'Alaih) and sources that not all scholars acknowledge and use (Mukhtalaf Fiih). Muttafaq 'Alaih sources are divided into two: those with no disagreement, and this type includes only two, the Qur'an and the Sunnah, while Muttafaq 'Alaih sources with some disagreement, although weak, also include two, Ijma' and Qiyas. Thus, the sources of Islamic law constitute a collection of evidence, and these pieces of evidence are sometimes revelations and sometimes not in the form of revelation.